Environmental effects of marine renewable energy off-grid and micro-grid applications: a use case approach to assess existing knowledge and remaining uncertainties (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Most environmental research and monitoring for marine renewable energy (MRE) devices has sought to understand effects that will drive consenting and licensing decisions for large, grid-scale, projects. However, many near-term and likely long-term uses of MRE will be to power remote coastal and island communities via micro-grids and direct supply, as well as provide power at sea for offshore aquaculture, ocean observations and navigation markers, and other off-grid uses. These applications will operate on a much smaller scale than grid-connected MRE devices for regional or national utility scales. There has been little focus on the potential environmental effects for these increasingly more common micro-grid or off-grid uses. The smaller MRE devices required for these applications are likely to have different, and possibly less, environmental effects than large-scale MRE projects. The time is right to start exploring the potential environmental effects that might be expected from smaller scale (i.e., micro-grid and off-grid) wave, tidal, and other MRE devices and projects, and to determine what additional or different information and data may be needed to inform and streamline consenting for these projects. For this paper, we generated a series of hypothetical use cases of micro-grid and off-grid applications, some with an on-land electricity use (e.g., a small coastal community, medium size shipping port) and others with strictly at-sea usages (e.g., oceanographic instruments, aquaculture farms). To set up the stage for each use case, we compiled a physical description of the deployment area, details about the MRE technology foreseen, information about the end uses and power needs, and a description of the local community and values. For each use case, we then inventoried the species of regulatory concern known to the hypothetical project area, as well as commercial and recreational species, important habitats, potential environmental interactions with the MRE device and infrastructure, and socio-economic benefits or concerns potentially associated with such project. In the absence of existing micro-grid or off-grid MRE projects, this use-case approach enabled an initial assessment of potential environmental effects, based on location and scale of the projects, which could then translate into recommendations for regulatory decisions.